2010
DOI: 10.1044/1058-0360(2010/09-0064)
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Language Nonword Repetition by Bilingual and Monolingual Children

Abstract: Purpose Identifying children with primary or specific language impairment (LI) in languages other than English continues to present a diagnostic challenge. This study examined the utility of English and Spanish nonword repetition (NWR) to identify children known to have LI. Method Participants were 4 groups of school-age children (N = 187). There were 2 typically developing groups: proficient Spanish-English sequential bilinguals and monolingual English speakers. There were 2 groups of children with LI, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
108
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 62 publications
20
108
2
4
Order By: Relevance
“…Previous studies have observed poorer oral language capacities in bilingual compared to monolingual children with SLI (Orgassa and Weerman, 2008;Westman, Korkman, Mickos, & Byring, 2008). However, other studies have failed to observe differences between the oral abilities of bilingual and monolingual children with SLI (Rothweiler, Chilla, & Clahsen, 2012;Windsor, Kohnert, Lobitz, & Pham, 2010) so evidence regarding this possibility is still inconclusive. Unfortunately, our study does not allow us to ascertain whether the increased percentage of reading deficit in our sample is due to bilingualism.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have observed poorer oral language capacities in bilingual compared to monolingual children with SLI (Orgassa and Weerman, 2008;Westman, Korkman, Mickos, & Byring, 2008). However, other studies have failed to observe differences between the oral abilities of bilingual and monolingual children with SLI (Rothweiler, Chilla, & Clahsen, 2012;Windsor, Kohnert, Lobitz, & Pham, 2010) so evidence regarding this possibility is still inconclusive. Unfortunately, our study does not allow us to ascertain whether the increased percentage of reading deficit in our sample is due to bilingualism.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the participants scored consistently high from the first time point (mean phonemes correct: 96%, SD = 2.8), even when their score on a standardized test of Icelandic was significantly below average. The conclusion was that NWR can be used even at beginning levels of L2 learning, a finding at odds with Windsor et al (2010) in that no disadvantage of bilingualism on NWR scores was evidenced, and it appears that the required level of language knowledge can be very low.…”
Section: Nwr In Bilingual Populationsmentioning
confidence: 80%
“…Elin Thordardottir and Brandeker (2013) confirmed this for both monolingual and bilingual children with PLI but showed that typically developing bilingual children were not disproportionately affected by nonword length. Other studies that have examined nonword length effects in bilingual children include Ebert, Kalanek, Cordero, and Kohnert (2008) and Windsor et al (2010). Ebert et al (2008) developed an NWR task in Spanish and assessed bilingual Spanish-English preschoolers.…”
Section: Properties Of Nonwords That Influence Performancementioning
confidence: 97%
See 1 more Smart Citation
“…So far, data on the incidence and prevalence of language disorders in the German population are missing. International epidemiological surveys converge in estimating the total population prevalence of language disorders at 9.92% [10] and the prevalence of DLD to be around 7% [11, 12]. However, as current prevalence estimates are based upon the general population in the UK and the USA, these findings must be regarded with caution, given the lack of reliable data on incidence and prevalence of language disorders in the culturally diverse population in Germany.…”
Section: Introductionmentioning
confidence: 90%